Metabolic engineering for enhanced oil in biomass - Vanhercke, Thomas; Dyer, John M.; Mullen, Robert T.; Kilaru, Aruna; Rahman, Md. Mahbubur; Petrie, James R.; Green, Allan G.; Yurchenko, Olga; Singh, Surinder P. (Progress in lipid research, 2019)
The world is hungry for energy. Plant oils in the form of triacylglycerol (TAG) are one of the most reduced storage forms of carbon found in nature and hence represent an excellent source of energy. The myriad of applications for plant oils range across foods, feeds, biofuels, and chemical feedstocks as a unique substitute for petroleum derivatives. Traditionally, plant oils are sourced either from oilseeds or tissues surrounding the seed (mesocarp). Most vegetative tissues, such as leaves and stems, however, accumulate relatively low levels of TAG. Since non-seed tissues constitute the majority of the plant biomass, metabolic engineering to improve their low-intrinsic TAG-biosynthetic capacity has recently attracted significant attention as a novel, sustainable and potentially high-yielding oil production platform. While initial attempts predominantly targeted single genes, recent combinatorial metabolic engineering strategies have focused on the simultaneous optimization of oil synthesis, packaging and degradation pathways (i.e., ‘push, pull, package and protect’). This holistic approach has resulted in dramatic, seed-like TAG levels in vegetative tissues. With the first proof of concept hurdle addressed, new challenges and opportunities emerge, including engineering fatty acid profile, translation into agronomic crops, extraction, and downstream processing to deliver accessible and sustainable bioenergy.